The Natural Product Andrographolide Ameliorates Calcific Aortic Valve Disease by Regulating the Proliferation of Valve Interstitial Cells via the MAPK-ERK Pathway - Yuming Huang; Ming Liu; Chungeng Liu; Nianguo Dong; Liang Chen (Frontiers Media S.A., 2022)
Calcific aortic valve disease (CAVD) is an active pathobiological process that involves fibrosis and calcification of aortic valve leaflets, thereby causing cardiac hemodynamic changes and eventually heart failure. Cell proliferation changes at the initial stage of CAVD are an important target for pharmaceutical intervention. This study aimed to investigate whether andrographolide (AGP) could inhibit the proliferation of valve interstitial cells (VICs) in vitro and in vivo to delay the process of CAVD. Cell proliferative factors were tested in both healthy and CAVD aortic valve samples. Cell cycle, cell growth, and calcification of VICs were assessed using flow cytometry, CCK8 assay, EdU staining, and Alizarin Red S staining. The expression of cell proliferative factors and osteogenic factors were quantified by qRT-PCR or immunofluorescence staining. The interaction between AGP and ERK (extracellular regulated protein kinases) was detected by molecular docking. In addition, a high-fat diet-fed animal model was used to verify the effect of AGP on CAVD in vivo. In conclusion, we found that AGP ameliorates aortic valve incrassation by inhibiting cell proliferation via the MAPK-ERK signaling pathway. Therefore, AGP is a promising drug that prevents the occurrence of CAVD via regulating cell proliferation.